Quevedo epigramático - López Poza, Sagrario (Aurea poesis: estudios para Begoña López Bueno, 2014)
In this work the poetic production of Francisco de Quevedo which can be considered epigrams is analyzed to obtain information about his particular embodiment of this poetic category. Based on the generic parameters of the Spanish Golden Age epigram, deduced from a thorough analysis on the treatises on the genre written in Latin, Spanish and other modern languages, and on previous work about this poetic form applied to the production of spanish Golden Age authors, we attempt to draw some conclusions about the epigrammatic modalities preferred by Quevedo, the dates in which the poet wrote more compositions of this type, the metric forms of choice for the composition of his epigrams, the internal structure that used to employ and predominant style traits.